Exploring potentials of Electuaries for Controlling Chronic Respiratory Diseases in Unani Medicine: A Systematic Review - Khan, Muzayyana; Akhlaq, Shaheen; Shamsi, Shariq (Current Traditional Medicine, 2024)
Background: Chronic respiratory diseases rate has been increasing alarmingly, causing huge burden on the mortality and morbidity. Environmental pollution and occupational exposure, the major identified risk factors and endless adverse effects of conventional medicine put forward the need for better alternative options. Electuaries are the pharmaceutical formulation of poly herbal drugs that are employed as effective remedy for respiratory disorders in Unani system of medicine. Objective: The aim is to assess the effectiveness of Unani pharmaco-therapeutics in the management of various respiratory diseases and the computation of drug/water and drug/sugar ratio for the elaborated electuaries. Methods: A web-based review on certain selected Unani drugs and its molecular mechanism was carried out using the data bases such as Pub Med, Google Scholar, Science Direct and Scopus published until the end of June 2022. Results: It was observed that several single drugs such as Khayarshambar (Cassia fistula L.), Sapistan (Cordia dichotama Forst), Asl-us- Soos (Glycyrrhiza glabra L.), Khatmi (Althea officianialis L.), Za’fran (Crocus sativus L.), BehīdĦ#129;na (Cydonia oblonga Mill.) etc. used in Unani formulations claimed to be effective in management of respiratory diseases like COVID 19. The herbs and its chemical constituents showed the preventive effect on respiratory diseases with inflammatory cell mediators, lung pathologies, airway response and immunomodulatory effects. The results of research studies (preclinical, clinical or in silico) and their molecular mechanisms on Electuaries have proved to be optimal for the respiratory system. Conclusion: Unani poly-pharmaceutics showed anti-inflammatory, anti-viral, anti-bacterial, antiallergic, anti- tussive, mucolytic actions arresting respiratory diseases.
Keywords: electuaries